Bjerndrup - et skattefund med bebyggelse fra vikingetiden - Brøgger, Søren; Hartvig, Anders (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
In the early part of 2018, three metal detectorists discovered several Viking Age silver coins on a field near the village of Bjerndrup in the southeastern part of Jutland, Denmark. Local archaeologists were contacted and in cooperation with the landowner they were able to excavate the area during two campaigns in 2018 and 2019 – excavations in which the original finders took part with their metal detectors. The excavations revealed 224 pieces of silver: 150 coins or fragments of coins, fourteen silver ingots and sixty pieces of hack silver. The coins were Kufic, Anglo- Saxon, Frankish, and Danish, from the emporia Ribe and Hedeby. The date of the younger coins suggests that the hoard was buried not long after 910 AD. The removal of the topsoil revealed a longhouse, three smaller buildings and nineteen sunken-feature-buildings (SFBs). The longhouse was 14C-dated to c. 945 – 993 AD, while some of the other buildings appear to be a bit older. The SFBs contained spindle whorls and loom weights indicating textile production. One SFB stood out as it contained e. g. glass beads, a miniature silver sword, and a Thor’s hammer amulet. The combination of coins and especially the presence of coins from both Hedeby and Ribe sheds new light on early Danish coinage and trading between Ribe and Hedeby.